The Influence of Brand Image and Celebrity Endorsers on Sales of Skincare Products The Originote - Rokhim, Lisna Nur; Riyanto, Kuwat (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This research aims to analyze the influence of brand image and celebrity endorsers on sales of The Originote skincare products. The research uses quantitative methods with respondents who are consumers of The Originote. Data was collected through questionnaires and analyzed with SmartPLS. The research results show that there is a significant influence of celebrity endorsers on sales of The Originote skincare products. There is a significant influence of brand image on sales of The Originote skincare products. The celebrity endorser and brand image variables are able to explain variations in sales of The Originote skincare products. The conclusion of this research is that celebrity endorsers and a positive brand image have a big influence in attracting consumer buying interest which ultimately can increase sales of The Originote skincare products.